Public Archaeologies of Frontiers and Borderlands - Gleave, Kieran (Archaeopress, 2021)
Select proceedings of the 4th University of Chester Archaeology Student conference (Chester, 20 March 2019) investigate real-world ancient and modern frontier works, the significance of graffiti, material culture, monuments and wall-building, as well as fictional representations of borders and walls in the arts, as public archaeology.